Jackie Robinson : American hero - Robinson, Sharon 1950- (New York : Scholastic, 2013)
The life and career of Jackie Robinson.
Keywords: Baseball players -- United States -- Biography -- Juvenile literature; African American baseball players -- Biography -- Juvenile literature